Pediatric Feeding Disorders and Severe Developmental Disabilities - Kleinert, Jane ORegan (Seminars in Speech and Language, 2017)
Children with severe developmental disabilities face numerous challenges to function and participate in activities of daily life. One of the most significant challenges to accomplishing this goal is that of oral feeding disorders. Indeed, it is estimated that among children with developmental disabilities, up to 80 to 90% present with some level of feeding disorders. In addition, it has been shown that as the level of severity of intellectual disability increases, so does the severity of the oral feeding disorders. Due to the broad range of etiologies that result in developmental disabilities, types of feeding disorders in the population vary greatly. This article is designed to provide information regarding assessment and intervention approaches currently used in this area and to provide an overview of the evidence available to support these approaches. Suggestions for much needed future clinically relevant and immediately transferable research are included.
Keywords: Pediatric feeding disorders; developmental disabilities; dysphagia